Pendidikan Kesehatan tentang Perawatan Kaki pada Keluarga Lansia dengan Diabetes Melitus di Wilayah Kerja Puskesmas Kayon Kota Palangka Raya - Meity Kristine Mewo; Berthiana Berthiana (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Epidemiological data suggest that approximately 30% to 40% of adults with type 2 diabetes have distal peripheral neuropathy (DPN), at risk for foot ulcers (diabetic ulcers). That is the importance of applying science in performing foot care. The results of the implementation of community service that have been carried out show an increase in the knowledge of participants (elderly families) after health education about foot care in the elderly with DM and awareness of the elderly in independence in carrying out daily activities will improve the quality of life and health of the elderly. The conclusion from the implementation of community service participants in community service can understand and understand the role of the family about the importance of foot care. There are two evaluations carried out in this community service, namely: Pre-test and post-test evaluations, namely in the pretest activities, the results of the 25 participants were 40% good and 60% bad after the post-test activity was carried out, the score was 80% good and 20% bad.